Modeling the potential public health impact of different vaccination strategies with an omicron-adapted bivalent vaccine in Malaysia - Karan Thakkar; Julia Spinardi; Moe H. Kyaw; Jingyan Yang; Carlos Fernando Mendoza; Mohan Dass; William Law; Egemen Ozbilgili; Ben Yarnoff (Taylor & Francis Group, 2023)
Background Coronavirus disease 2019 (COVID-19) case numbers have increased following the emergence of the Omicron variant. This study estimated the impact of introducing and increasing the coverage of an Omicron-adapted bivalent booster vaccine in Malaysia. Research Design and Methods A combined cohort Markov decision tree model was used to compare booster vaccination with an Omicron-adapted bivalent COVID-19 vaccine versus no booster vaccination in Malaysia. The model utilized age-specific data from January 2021 to March 2022 derived from published sources. The outcomes of interest included case numbers, hospitalizations, deaths, medical costs, and productivity losses. The population was stratified into high-risk and standard-risk subpopulations, and the study evaluated the benefits of increased coverage in different age and risk groups. Results Vaccinating only high-risk individuals and those aged ≥ 65 years was estimated to avert 274,313 cases, 33229 hospitalizations, 2,434 deaths, Malaysian ringgit (MYR) 576 million in direct medical costs, and MYR 579 million in indirect costs. Expanding vaccination coverage in the standard-risk population to 75% was estimated to avert more deaths (31%), hospitalizations (155%), infections (206%), direct costs (206%), and indirect costs (281%). Conclusions These findings support broader population Omicron-adapted bivalent booster vaccination in Malaysia with potential for significant health and economic gains.